BIBLIOTECA SERVICIILOR PROFESIONALE SAU PROIECTIZAREA DIMENSIUNII ACTUALE A ACTIVITĂŢII NOASTRE - KULIKOVSKI, Conf. univ. dr., director, Departamentul studii şi cercetări, Lidia (BIBLIOPOLIS, 2020)
The approach focuses on guidance, assistance in converting the workplace / space / structure of librarians in professional services. The ideas of transformation are based on conversion tools of Tom Peters adapted to the library. Each of the 28 steps / principles are explained by examples from the experience of the Municipal Library. The value comes from professional services. This is proved by the author, through tools, examples and conclusive stories. The conclusion of the author is limited to creating projects that means changes, innovation, implementation of a new service, user inclusion, the involvement of partners – an inherent requirements and new paradigms of library domain.